CSA Scholars' Roundtable Presentation: Design and Curatorial Scholarship: Purpose, Place, Present, and Future. (3rd July 2021) - DePauw, Karen; Morris, Kristen; Pisano, Linda; Sanders, Eulanda; Scaturro, Sarah; Reddy-Best, Kelly L.; Keist, Carmen
Abstract : The Costume Society of America (CSA) Scholars' Roundtable Honor committee is charged with nominating scholars to lead a discussion at the national symposium that challenges the organization members to think about future possibilities. In 2021, five CSA Scholars' Roundtable Honorees (Karen DePauw, Kristen Morris, Linda Pisano, Eulanda Sanders, and Sarah Scaturro) discussed the purpose, place, and future of design and curatorial scholarship. In this session, Kelly L. Reddy-Best and Carmen Keist, 2019 honorees, moderated the session. Carmen began by asking the panelists questions such as "In what ways can CSA be flexible to allow for new directions in scholarship?" This year, CSA held the symposium digitally due to COVID-19. Following the pre-prepared questions, individuals from the audience offered comments and questions to the panel via the chat box. In this paper, we provide a verbatim transcription of the session.